(untitled) (Editora Impacto Científico, 2025)
The locality of Tiáia, located in the district of Parazinho, municipality of Granja (Ceará, Brazil), with about 1,219 inhabitants (IBGE, 2022), has its origins linked to the Tremembé people, whose territory was first officially recorded in 1706 with the granting of sesmarias. The name, of Tupi origin, means “sour water” or “water point.” Since the colonial period, it has been marked by the imposition of Christian and capitalist logics, which transformed the Indigenous way of life—based on a sense of belonging to the land—into mercantile exploitation, especially through cattle raising, cotton, salt, and carnauba, consolidating socio-environmental inequalities and the invisibilization of native peoples, often classified as “caboclos” in 19th-century censuses. Despite land losses, environmental degradation, and precarious access to basic resources, the community preserves ancestral practices of resistance, such as subsistence farming, sustainable water management, and the use of medicinal plants, orally transmitted across generations. These knowledges, combined with the strong symbolic relationship with “mother earth,” serve as instruments of identity and resistance against capitalist exploitation and cultural homogenization. Thus, the study shows that Tiáia’s historical trajectory is marked by exclusion but also by the continuity of practices that reaffirm community and environmental bonds. DOI: https://doi.org/10.56238/edimpacto2025.090-025